Indonesian EFL Students’ Perception of Educational Philosophy - Lobi, Yohanes Capistrano Satrini; Ena, Ouda Teda (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2024)
Abstract. Each student possesses a personal philosophy that influences their educational journey. Adopting and implementing specific educational philosophies serve as a guiding framework for students to attain optimal future outcomes. Hence, it is crucial to explore the educational philosophy and its consequences. This article investigates English Education Students’ philosophy of education. The data were collected from 29 students using questionnaires with 40 questions in which participants were to rate statements related to their educational philosophy. A 5-point Likert scale was used to measure participants’ attitudes towards and perceptions of the educational philosophies. The results indicated that most participants adhered to the humanism educational philosophy, while a few had a diverse and inclusive perspective. The findings enhance comprehension of the approaches Indonesian EFL students choose in their studies and provide guidance for educators to customize their teaching techniques to correspond with these perceptions. The findings show that the majority of the EFL preservice teachers are inclined toward a humanistic educational philosophy. The educational implication is that they would assume the role of a teacher who focuses on the development of the whole person, focusing on students’ emotional, intellectual, and social growth in their later teaching career.Keywords: curriculum, educational philosophy, EFL students, teacher candidates